Machine translation, its prospects, challenges, and the efforts of Arab scholars in this field - bouras, slimane; abdelmoumene, ali (El Omda in Linguistics and Discourse Analysis, 2025)
Abstract: Arab researchers' efforts in developing Arabic automated translation Abstract: Since the technological revolution, translation has taken a new form that is more flexible, easier and more useful; since it become a purely automated work based on computer accountability, and having witnessed an increasing turnout especially in industry and trade. Since translation is a natural means of learning foreign languages among Arabs and others, the emergence of automated translation, Arabic has sought to apply it in all its research and uses. Today, it is proceeding in this endeavor to achieve its goals and serve its objectives. In doing so, it has made great efforts to elaborate a good informatic system for automated translation. Performant Arabic automated programs and systems have emerged. It achieved Arabic language goals and purposes that human beings have been unable to attain before. However, it needed further development, some programs need to be restructured and formulated in order to be more effective and better performing, in order to counter the dominance of foreign languages that had swept across all fields, and extended their shade over all AI products so that Arabic could hardly find a place among the world's languages.